An additive manufacturing oriented design approach to mechanical assemblies. Issue 1 (15th November 2017) - Sossou, Germain; Demoly, Frédéric; Montavon, Ghislain; Gomes, Samuel
Graphical abstract: Abstract: Firstly introduced as a prototyping process, additive manufacturing (AM) is being more and more considered as a fully-edged manufacturing process. The number of AM processes, along with the range of processed materials are expanding. AM has made manufacturable shapes that were too difficult (or even impossible) to manufacture with conventional technologies. This has promoted a shift in engineering design, from conventional design for manufacturing and assembly to design for additive manufacturing (DFAM). Research efforts into the DFAM field have been mostly dedicated to part's design, which is actually a requirement for a better industrial adoption. This has given rise to topologically optimized and/or latticed designs. However, since AM is also capable of manufacturing fully functional assemblies requiring a few or no assembly operations, there is a need for DFAM methodologies tackling product's development more holistically, and which are, therefore, dedicated to assembly design. Considering all the manufacturing issues related to AM of assembly-free mechanisms and available post-processing capabilities, this paper proposes a top-down assembly design methodology for AM in a proactive manner. Such an approach, can be seen as the beginning of a shift from conventional design for assembly (DFA) to a new paradigm. From a product's concept and a selected AM technology, the approach first provides assistance in the definition of the product architecture so that both functionality and successful manufacturing (including post-processing) are ensured. Particularly, build-orientation and downstream processes' characteristics are taken into account early in the design process. Secondly, for the functional flow (energy, material, signal) to be appropriately conveyed by the right amount of matter, the methodology provides guidance into how the components can be designed in a minimalism fashion leveraging the shape complexity afforded by AM. A mechanical assembly as case study is presented to illustrate the DFAM methodology. It is found that clearances and material (be it raw unprocessed material or support structures) within them plays a pivotal role in a successful assembly's design to be additively manufactured. In addition, the methodology for components' design proves to be an efficient alternative to topology optimization. Though, the approach can be extended by considering a strategy for part consolidation and the possibility to manufacture the assemblies with more than one AM process. As regards components' design, considering anisotropy can also improved the approach.